A 4_bit ultra_wideband complementary metal_oxide_semiconductor attenuator with low root_mean_square amplitude error - Chatrpol Pakasiri; Fu_Sheng Zhu; Sen Wang (My University, 2019)
This article presents the 4-bit ultra-wideband complementary metal-oxide-semiconductor (CMOS) attenuator in a standard 0.18-μm CMOS process. This design adopts switched bridge-T type topologies for each attenuation bit. Based on insertion losses and input P1-dB considerations, the circuit performances can be optimized by the proper bit ordering arrangement. Therefore, the bit ordering 0.5-4-2-1 dB is employed in the 4-bit attenuator. Moreover, series inductors are added between each bit to further improve the input and output return losses. Measured results demonstrate that the attenuation range of the circuit is 7.5 dB with 0.5 dB step and the root-mean-square (RMS) amplitude error is between 0.11 and 0.13 dB from 3.1 to 10.8 GHz. The differences between simulated and measured RMS amplitude errors are less than 0.2 dB, which demonstrates the good agreement and feasibility of the design concept. The measured input P1-dB is 15 dBm at 5 GHz and the chip area is 1.12 mm2 including all testing pads.
Keywords: Attenuator (electronics); Return loss; Wideband; Root mean square; Radio Frequency Integrated Circuit Design